Socioeconomic Dimensions of German Language Proficiency Among Descendants of the Pre-War Population of Masuria: Narratives from Field Research - Piotr Szatkowski (Acta Baltico-Slavica)
This paper examines the ways of using the German language by descendants of pre-war inhabitants of Masuria. A series of semi-structured and unstructured interviews (over 50, 48 of which were transcribed) conducted during field research throughout Masuria showed that the higher proficiency in German, or at least a less negative attitude towards German compared to the general population of the region, resulted in better socioeconomic chances after the collapse of communism in Poland. Many descendants of pre-war Masurians have used the knowledge of German in education, business, teaching, translation, and NGOs, giving them better chances to adapt to the new, capitalist economy. It was particularly important in the 1990s and 2000s, when Masuria suffered high unemployment rates. The field research was conducted using multiple snowball sampling in Lutheran parishes, German minority organisations and regional NGOs, and local communities.